1993
DOI: 10.2307/1542481
|View full text |Cite
|
Sign up to set email alerts
|

Shell Growth and Viability Differences Between the Marine Mussels Mytilus edulis (L.), Mytilus galloprovincialis (Lmk.), and Their Hybrids From Two Sympatric Populations in S.W. England

Abstract: Mussels were collected at high and low shore locations from two Mytilus edulis/Mytilus galloprovincialis populations, Croyde Bay and Whitsand Bay, in S.W. England. Genotype-dependent length-at-age values were determined. At high and low shore locations at both sites, M. edulis-like mussels had significantly smaller length-at-age values than M. galloprovincialis-like and putative F1 hybrid individuals. The putative F1 hybrids exhibited length-at-age values between those of the parental types, but much closer to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
42
0
2

Year Published

1996
1996
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(46 citation statements)
references
References 32 publications
2
42
0
2
Order By: Relevance
“…4). These results are in line with those found for English populations (Skibinski, 1983;Gardner & Skibinski, t988;Skibinski & Roderick, 1991;Gardner et at., 1993). No such correlation was found for Irish exposed populations (Gosling & McGrath, 1990), and tt may be explained because only a low percentage of mussels greater than 8 mm in length were considered (Gardner, 1994}.…”
Section: (25"/)supporting
confidence: 92%
See 1 more Smart Citation
“…4). These results are in line with those found for English populations (Skibinski, 1983;Gardner & Skibinski, t988;Skibinski & Roderick, 1991;Gardner et at., 1993). No such correlation was found for Irish exposed populations (Gosling & McGrath, 1990), and tt may be explained because only a low percentage of mussels greater than 8 mm in length were considered (Gardner, 1994}.…”
Section: (25"/)supporting
confidence: 92%
“…With regard to the stability of the hybrid zone in time, homogeneity chi-square test for allele frequencies at diagnostic and non-diagnostic loci showed no significant differences between populations from the same place sampled in 1988 (CFA) and 1992 (C4A) (data not shown; see Table 2). This can be taken as evidence that both samples exhibit short-term temporal genetic stability and supports the idea that Mytilus hybrid zones are stable in structure (Gardner & Skibinski, 1988;Beaumont et al, 1989;Gardner et al, 1993). Nevertheless, Viard et al (1994) report strong genetic changes in time in their samples in the French hybrid zone after 3 years, but ecological data are not reported.…”
Section: (25"/)supporting
confidence: 75%
“…The difference between the results obtained from larvae (this study) and from adults (Rawson et al, 1996) suggests that hybrid individuals in which DUI has been disrupted might suffer greater mortality between 72 h and adulthood than mussels in which DUI has not been disrupted. There is evidence from a number of studies that adult M. edulis  M. galloprovincialis hybrids on average have a fitness approximately equal to M. galloprovincialis and higher than M. edulis, in terms of viability (Gardner and Skibinski, 1991;Willis and Skibinski, 1992;Gardner et al, 1993), developmental stability and developmental rate (Gardner, 1995), growth rate (Gardner et al, 1993), fertility and fecundity (Gardner and Skibinski, 1990) and resistance to parasites (Coustau et al, 1991). Previous studies of laboratory hybridizations between M. edulis and M. galloprovincialis showed no difference in the viability of early (up to 2 or 3 days) hybrid larvae compared to pure species larvae (Beaumont et al, 1993;Bierne et al, 2002;our unpublished data).…”
Section: Discussionmentioning
confidence: 99%
“…Rawson and Hilbish (1998) failed to find evidence of mtDNA introgression from Mediterranean M. galloprovincialis to M. edulis, and suggested that directional selection favouring M. galloprovincialis nuclear alleles over those of M. edulis might remove those hybrid mussels with predominantly M. edulis nuclear genotypes. Such selection has been shown to occur in hybrid populations Skibinski, 1988, 1991;Skibinski and Roderick, 1991;Gardner et al, 1993) and would have the effect of removing potentially introgressing M. galloprovincialis mitotypes but not those of M. edulis. Further studies would be necessary to determine whether either of these factors plays a significant role in restricting gene flow between M. edulis and M. galloprovincialis.…”
Section: Discussionmentioning
confidence: 99%
“…In a further 13 hybrid zones, patterns of introgression might be interpreted as evidence for movement: gulls Larus glaucescens and Larus occidentalis (Bell, 1996;Gay, 2006); pocket gophers Thomomys townsendii and Thomomys bottae (Patton, 1993;Patton and Smith, 1993); Thomomys bottae actuosus and Thomomys bottae ruidosae (Ruedi et al, 1997); fish Gambusia affinis and Gambusia holbrooki (Reznick, 1981;Scribner, 1993;Scribner and Avise, 1993;Scribner and Avise, 1994a, b); hares Lepus granatensis/Lepus europaeus and Lepus timidus (Thulin and Tegelströ m, 2002;Melo-Ferreira et al, 2005, 2007; salamander Chioglossa lusitanica North and South forms (Sequeira et al, 2005); mussels Mytilus galloprovincialis and Mytilus edulis (Gardner and Skibinski, 1988;Skibinski and Roderick, 1991;Willis and Skibinski, 1992;Gardner et al, 1993;Wilhelm and Hilbish, 1998;Bierne et al, 2003); beetles Carabus albrechti and Carabus lewisianus (Takami and Suzuki, 2005); lizard Sceloporus grammicus chromosomal races F5 and FM2 (Sites et al, 1996;Marshall and Sites, 2001) cottonwoods Populus angustifolia and Populus fremontii (Keim et al, 1989;Paige et al, 1991;Martinsen et al, 2001).…”
Section: Rja Buggsmentioning
confidence: 99%